Primary medical care in Irish prisons - Barry, Joe M (BioMed Central, 2010)
BACKGROUND: An industrial dispute between prison doctors and the Irish Prison Service (IPS) took place in 2004. Part of the resolution of that dispute was that an independent review of prison medical and support services be carried out by a University Department of Primary Care. The review took place in 2008 and we report here on the principal findings of that review. METHODS: This study utilised a mixed methods approach. An independent expert medical evaluator (one of the authors, DT) inspected the medical facilities, equipment and relevant custodial areas in eleven of the fourteen prisons within the IPS. Semistructured interviews took place with personnel who had operational responsibility for delivery of prison medical care. Prison doctors completed a questionnaire to elicit issues such as allocation of clinician's time, nurse and administrative support and resources available. RESULTS: There was wide variation in the standard of medical facilities and infrastructure provided across the IPS. The range of medical equipment available was generally below that of the equivalent general practice scheme in the community. There is inequality within the system with regard to the ratio of doctor-contracted time relative to the size of the prison population. There is limited administrative support, with the majority of prisons not having a medical secretary. There are few psychiatric or counselling sessions available. CONCLUSIONS: People in prison have a wide range of medical care needs and there is evidence to suggest that these needs are being met inconsistently in Irish prisons.